Rational design of multifunctional antibacterial coatings - He, Tao (2011)
The use of medical implants has significantly improved the survival and quality of lives of the world population and has been an indispensable procedure in health care industry nowadays. Biofilm formation, which is mainly composed of microorganisms within a protective extracellular matrix, is a major barrier in the long term utilization of the biomedical devices. Once biofilm is formed, it is extreme difficult to be removed due to its well-known drug resistance. Therefore, the best defensive strategy for combating medical device related infection is to prevent biofilm formation on the device surface. The anti-bacterial surface coating is one of the most effective ways for this purpose. In this thesis, two novel kinds of antibacterial surface coating were developed. The first antibacterial coating is based on polyelectrolyte multilayer film (PMF) with the incorporation of silver nanoparticles, a widely used antimicrobial agent. The PMF has only one polyelectrolyte building blockpolyethyleneimine (PEI) comparing with traditional two polyelectrolytes one, and silver (Ag) nanoparticles were incorporated into PEI multilayer via in situ reduction of Ag+. By varying PMF thickness and silver loading cycles, the mass of incorporated Ag nanoparticles can be controlled. It is shown that the PEI multilayer coating itself possesses considerable contact-killing properties against two types of bacteria.